ESTABLISHING PHYSICAL ACTIVITY OF 3RD - 4TH - GRADERS WITH ACCELEROMETERS - Oleg Hristov; Milena Zdravcheva; Borislava Petrova (Scientific Publishing House. NSA Press, 2022)
Adolescents' physical activity is and must be an essential part of their daily routine for proper and balanced growth and development. The use of accelerometry, a method that records the motor activity time spent in a lying or sitting position over twenty-four hours, is well-known. The actual data about a person's movements enables us to be accurate and even to analyze the quantity and quality of those movements. We examined 135 children (mean age 129 months) with accelerometers Axivity model AX3, positioned around the wrist around the non-dominant arm. Based on consults, we established average values per twenty-four hours, namely - an average of 38.32% of the time children spent in a sitting position, 6.41% (92 min) they were engaged in a low activity, 15.42% (222 min - in a moderate activity, 1.79% (26 min) - in a high activity; and 38.06% of the time they spent sleeping. We found a weak correlation dependence r = -.263 (95%) between the body fat and the duration of the time spent in high activity.